Hydroxyapatite-based materials of marine origin: A bioactivity and sintering study - Piccirillo C.; Pullar R. C.; Costa E.; Santos-Silva A.; Pintado M. M. E.; Castro P. M. L. (Materials Science and Engineering: C, 2015)
Single phase hydroxyapatite (HAp) and biphasic material hydroxyapatite/β-tricalcium phosphate (HAp/β-TCP) were obtained from a marine source (Atlantic cod fish bones). Here we report a study on the biological properties of these materials, including cytotoxicity, bioactivity and haemocompatibility. Results showed that the materials are not cytotoxic, neither in their powder nor in pellet form; indeed growth of Saos-2 cells was comparable to that of commercial. The haemolysis rate was lower than 2%; hence the materials can be classified as non-haemolytic. Moreover, when immersed in Simulated Body Fluid (SBF), crystal formation was observed on the surface of both materials. The sintering behaviour of the samples was also studied; both powders showed very high sinterability (density higher than 95% of the theoretical value). Overall, these results confirm the suitability of these materials for biomedical applications.